2008
DOI: 10.1038/ncpneph0847
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and anemia correction: surrogate markers or causes of morbidity in chronic kidney disease?

Abstract: Observational studies have shown a strong positive correlation between the severity of anemia and the risk of poor outcomes in patients with chronic kidney disease (CKD). This observation was initially taken to imply that adverse outcomes in CKD are caused by anemia. However, the assumption of causality ignores the possibility that anemia and adverse outcomes might be unrelated and that both are caused by underlying inflammation, oxidative stress and comorbid conditions. Randomized clinical trials of anemia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 112 publications
2
33
0
1
Order By: Relevance
“…However, recent studies have shown that full anemia correction in stage 3 to 4 CKD patients may be harmful (1,2). Such an effect is currently attributed to the deleterious action of high doses of erythropoietin imposed by erythropoietin resistance in patients with systemic illness and inflammation (3). Even though a recent secondary analysis of one of these studies (4) offers solid support to this hypothesis, other mechanisms also may be at play (3).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…However, recent studies have shown that full anemia correction in stage 3 to 4 CKD patients may be harmful (1,2). Such an effect is currently attributed to the deleterious action of high doses of erythropoietin imposed by erythropoietin resistance in patients with systemic illness and inflammation (3). Even though a recent secondary analysis of one of these studies (4) offers solid support to this hypothesis, other mechanisms also may be at play (3).…”
mentioning
confidence: 88%
“…Such an effect is currently attributed to the deleterious action of high doses of erythropoietin imposed by erythropoietin resistance in patients with systemic illness and inflammation (3). Even though a recent secondary analysis of one of these studies (4) offers solid support to this hypothesis, other mechanisms also may be at play (3). Because Hb is a well recognized carrier and buffer of nitric oxide (NO), which modulates the bioavailability of this compound at tissue level (5), disturbed regulation of endothelial function secondary to changes in Hb concentration appears to be a relevant pathophysiologic pathway whereby changes in red cell mass may exert adverse cardiovascular events (6).…”
mentioning
confidence: 99%
“…A anemia se associa com evolução adversa da DRC, incluindo hospitalização, doença cardiovascular, mortalidade e diminuição da qualidade de vida dos pacientes. 23 A principal causa de anemia na DRC é a deficiência de produção da eritropoietina pelos fibroblastos peritubulares renais. 24 Contudo, é importante mencionar que outros fatores podem determinar a ocorrência de anemia nesses pacientes, particularmente a deficiência de ferro.…”
Section: Figura -Avaliação Da Proteinúria Em Indivíduos De Grupo De Runclassified
“…This trend could potentially be harmful because iron could 6 amplify oxidative stress and inflammation, which are constant features of CKD/ESRD. [7][8][9][10] The potential role of high doses of ESA in the pathogenesis of cardiovascular disease (CVD), thromboembolic disorders, and other complications has been reviewed previously 11,12 and will not be addressed here. This article provides an overview of the potential safety concerns with use of iron preparations.…”
mentioning
confidence: 99%